Half Moon Street - Perry, Anne (Perry, Anne. Charlotte and Thomas Pitt novel., 2000)
For Superintendent Thomas Pitt, the sight of the dead man riding the morning tide of the Thames is unforgettable. The corpse lies in a battered punt drifting through the early mist, clad in a torn green gown and bestrewn with flowers. Pitt<U+2019>s determined search for answers to the victim<U+2019>s identity leads him deep into London<U+2019>s bohemia<U+2014>to the theatre where beautiful Cecily Antrim is outraging society with her bold portrayal of a modern woman, and into studios where masters of light and shadow are experimenting with the fascinating new art of photography. But only Pitt<U+2019>s masterly investigative skills enable him to identify the wildfire passions raging through this tragedy of good and evil, to hunt down the guilty and protect the innocent.